2003
DOI: 10.1097/01.ccm.0000050074.82486.b2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mitochondrial function induced by serum from septic shock patients is attenuated by inhibition of nitric oxide synthase and poly(ADP-ribose) synthase*

Abstract: In vitro mitochondrial respiration was significantly depressed by septic serum. The addition of N(G)-methyl-L-arginine, a nitric oxide synthase inhibitor, and 3-aminobenzamide, a blocker of the poly(ADP-ribose) synthase pathway, significantly attenuated this suppression. These data suggest that nitric oxide and poly(ADP-ribose) synthase activation may play an important role in the inhibition of mitochondrial respiration in septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…87,88 Mitochondria are known to be a major intracellular source of ROS, 59 and incubation of cells in plasma taken from septic patients results in a marked depression of mitochondrial respiration with associated oxidative stress. 89 A relationship between sluggish microvascular flow and oxidative stress in AKI is now coming to the forefront. Oxidative stress in renal tubules has been coupled closely with sluggish blood flow in adjacent capillaries.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…87,88 Mitochondria are known to be a major intracellular source of ROS, 59 and incubation of cells in plasma taken from septic patients results in a marked depression of mitochondrial respiration with associated oxidative stress. 89 A relationship between sluggish microvascular flow and oxidative stress in AKI is now coming to the forefront. Oxidative stress in renal tubules has been coupled closely with sluggish blood flow in adjacent capillaries.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Moreover, mitochondrial dysfunction has been shown to be a key mechanism involved in organ failure, the hallmark of sepsis. One study demonstrated that serum from septic shock patients significantly impaired mitochondrial respiration in endothelial cells and decreased cellular ATP levels [9]. Previous studies have indicated that autophagy is associated with reduced intracellular ATP levels [10].…”
Section: Introductionmentioning
confidence: 98%
“…In vitro, there is a significant correlation between SvO 2 and impairment of mitochondrial oxygen utilization. 42 The resultant tissue hypoxia can serve to further activate endothelial mediators, 22 causing loss of vascular integrity, 43 increased release of inflammatory cytokines 44 and procoagulants, 45 and reduced fibrinolysis. 46 …”
Section: Oxygen Transport and Utilizationmentioning
confidence: 99%